1986
DOI: 10.1111/j.1365-2672.1986.tb05090.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistant bacteria in Windermere and two remote upland tarns in the English Lake District

Abstract: The incidence of antibiotic resistance was determined in over 2000 bacteria which were divided into the following groups: faecal streptococci, coliforms (excluding Escherichia coli), E. coli, Pseudomonas spp. and aquatic bacteria (i.e. bacteria predominant in the lake water which were excluded from the previous four categories). The isolates were obtained from the water of Windermere (English Lake District) and from a sewage effluent which entered the lake. With the exception of the faecal streptococci, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 22 publications
1
47
1
Order By: Relevance
“…For example, both ampicillin and cephalothin are inactivated by chromosomal beta-lactamases produced by many enterobacterial (17) and Aeromonas (40) species. Most studies on bacterial antibiotic resistances in sewage (3,18), freshwater (3,9,27,33,34), and seawater (8,38) did not take into account these elements, leading to unexpected conclusions. For example, Jones et al (27) found a higher incidence of resistance in the bacteria isolated from remote upland tarns than in those isolated from a polluted lake or a sewage, with the highest values being observed for pseudomonads, which are naturally multiresistant organisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, both ampicillin and cephalothin are inactivated by chromosomal beta-lactamases produced by many enterobacterial (17) and Aeromonas (40) species. Most studies on bacterial antibiotic resistances in sewage (3,18), freshwater (3,9,27,33,34), and seawater (8,38) did not take into account these elements, leading to unexpected conclusions. For example, Jones et al (27) found a higher incidence of resistance in the bacteria isolated from remote upland tarns than in those isolated from a polluted lake or a sewage, with the highest values being observed for pseudomonads, which are naturally multiresistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Urban effluents are known to contain high levels of antibiotics and antibiotic-resistant bacteria belonging to the human and animal commensal flora, mainly Enterobacteriaceae (9,22,27). In order to study the impact of an urban effluent on the antimicrobial resistance of the microbial riverine flora, the acquired antibiotic resistance rates of enterobacteria and Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, Jones and his colleagues (1986b) have also emphasized that the methods and media used in detecting antibiotic-resistant bacteria affect the results. The level of antibiotic resistance in the environment is also affected by the location of the samples taken and the species of bacteria isolated (Jones et al 1986a, b). In the present study, differences in the overall proportions of antimicrobial resistance at the sampling sites may be partly explained by differences in the proportions of different bacterial species isolated (Table 4).…”
Section: Discussionmentioning
confidence: 64%
“…However, the tolerance to heavy metal toxicity can also be influenced by several environmental factors like constituents of ecosystem, ion interactions, pH, the form and availability of metals to the microbes. Thus, bacterial tolerance to metal toxicity is a significant environmental phenomenon (Sterritt and Lester, 1980;Jones et al, 1986).…”
Section: Discussionmentioning
confidence: 99%